The effect of different salt and phosphate levels of frozen hen meats on emulsion characteristics - Seher Kaya; Ramazan Gökçe; Hüsnü Yusuf Gökalp (Eurasian Journal of Veterinary Sciences)
In this research, meat samples have been taken from breast and thigh parts of old hen carcasses. Samples have been frozen at -25±1ºC and stored at -18 ºC for 2 months. Three diflerent types of meat: breast meat, thigh meat and their mixture of 1:1 ratio were used as materials. Prepared emulsions were studied that the effect of 3 salt levels (1%, 1,5%, 2,5%), 2 phosphate levels (0.25% and 0.50%) on emulsion capacities (EC) and on emulsion stabilities (ES) of these samples. Frozen breast meat had also higher EC and ES values than thigh meat and mixed meat. Emulsions that prepared with the frozen thigh meat were broken during the heating process. According to the sail levefs 2.5% salt level gave the highest EC and ES values in all treatments. In the frozen breast and mixed meat samples, the 0.5% phosphate added emulsions gave the highest ES values. According to statistically significant level it was concluded that different phosphate levels has not effected EC.